1988
DOI: 10.1007/bf02226810
|View full text |Cite
|
Sign up to set email alerts
|

Association between N2-fixing bacteria and pearl millet plants: Responses, mechanisms and persistence

Abstract: Responses to inoculation with Nl-fixing bacteria were studied" in relation to genotypic differences in pea~1 millet, effect of nitrogen levels, and FYM additions in India. In some experiments, inoculation increased mean grain yield up to 33% over the uninoculated control, whereas in the remaining 11 experiments'there was no significant increase. Increased grain yields~ > 10% over the uninoculated controls were observed in' 46% of the experiments with AzospiriJ/um lipojerum (18.7% average increase) and with Azo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Mubassara et al (2008) had shown that Bio-fertilizers have improved quantity and quality features of wheat. In general Nitro kara followed can increase by positive influence on macro elements absorption such as N, P and K (Narula et al, 2000), micro elements such as Zn and Fe (Wani et al, 1988), improving water distributing in plant, developing Nitrate Redoctaz activity and finally producing plant hormones which have an important role in plant growth. These results are agreed with Singh et al (2004) who believed to maximize production of different wheat cultivars which inoculated with Azotobacter under normal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Mubassara et al (2008) had shown that Bio-fertilizers have improved quantity and quality features of wheat. In general Nitro kara followed can increase by positive influence on macro elements absorption such as N, P and K (Narula et al, 2000), micro elements such as Zn and Fe (Wani et al, 1988), improving water distributing in plant, developing Nitrate Redoctaz activity and finally producing plant hormones which have an important role in plant growth. These results are agreed with Singh et al (2004) who believed to maximize production of different wheat cultivars which inoculated with Azotobacter under normal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…More typically, no significant increase was observed (Wani et al, 1989) from inoculation with A. lipoferum. A similarly variable result was obtained from inoculation with Azotobacter chroococcum.…”
Section: Maizementioning
confidence: 97%
“…It could be attributed not only to N but also organic C contained in the fertilizer. Wani et al (1988) reported that the use of suitable farmyard manures, green manures and other organic manures and fertilizers may enhance the benefits of Azotobacter inoculation. This is due to the fact that the N-fixation reaction needs a lot of energy from available organic C to break the bonds between nitrogen atoms (Postage, 1998).…”
Section: Soil Propertiesmentioning
confidence: 99%